Potential of local Trichoderma in bioremediation of degraded soil - Ghifari, Bima Iqbal; Ridho, Muhammad Rasyid; Putri, Reggina Sonia; Wagino, Syahwa Fitria Maharani; Azizah, Wahda Zahra; Husna, Muhimmatul; Izzatuddinillah, Iffah; Arraudah, Rahayu (Journal of Earth Kingdom, 2026)
Background: Soil degradation in Indonesia is a serious challenge, impacting agricultural productivity and environmental quality. One potential ecological solution is bioremediation using soil microorganisms such as Trichoderma spp. This study aims to identify local Trichoderma isolates from various regions in Indonesia along with their biological and functional characteristics in the bioremediation process. Method: This study uses a narrative literature review to synthesize conceptual and empirical evidence from academic journals, scientific articles, and policy reports. This review focuses on assessing the biological and functional characteristics of local Trichoderma isolates and their effectiveness in addressing unsustainable soil management and environmental degradation. Finding: The results of the literature study indicate that species such as Trichoderma harzianum, Trichoderma viride, Trichoderma asperellum, and Trichoderma koningiopsis can degrade organic and inorganic pollutants, suppressing pathogens, and improving soil fertility. The potential of each isolate is strongly influenced by its environmental origin and type of pollutant, with high effectiveness recorded in ex-mining soil, agricultural land, and pesticide-contaminated areas. Further research and policy support from research institutions or relevant parties are needed so that local Trichoderma can be developed as a bioremediation agent in sustainable agricultural systems in Indonesia. Conclusion: Local Trichoderma species offer a significant and sustainable solution for restoring soil health in Indonesia, provided that challenges related to technology adoption and isolate data can be overcome. Future success depends on cross-sector collaboration to bridge the gap between laboratory research and field application, ensuring that these biological agents are optimized through farmer education and regulatory support. Novelty/Originality of this article: This study presents a comprehensive synthesis of native Indonesian Trichoderma isolates, identifying a direct relationship between their geographic origin and their specific multifunctional effectiveness.